IDENTIDADE VISUAL PARA UM JOGO DIDÁTICO DE MATEMÁTICA1 - Rodrigues, Gean Carlo Machado; Silva, José Paulo Medeiros Da; Mendonça, Barbara Gündel; Johann, Diane Meri Weiller (Salão do Conhecimento, 2017)
Projeto de extensão realizado no curso de Design da Unijuí